2019
DOI: 10.1111/jphs.12314
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to adverse drug reaction reporting in community practice in the UAE

Abstract: Objectives This study was aimed at quantification of the pharmacists under-reporting in the UAE community practice, and how do they respond to adverse drug events (ADEs) and the factors behind their acts. Methods A questionnaire-based technique is implemented in this study to quantify the factors contributing to under-reporting of pharmacists in the UAE. The questionnaire is randomly distributed to a sample of 230 pharmacists throughout the UAE. Pharmacists responded either online or manually. Chi-square and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, globally, community pharmacists in Australia, Nigeria and the UAE were not aware of the ADR reporting programs in their countries. [14][15][16] In addition to awareness among community pharmacists, the role of regulatory authorities is also questionable due to the lack of implementation of regulations in community pharmacy practice. 10 The survey included community pharmacist's from one city in Saudi Arabia which limits its generalization.…”
Section: Resultsmentioning
confidence: 99%
“…However, globally, community pharmacists in Australia, Nigeria and the UAE were not aware of the ADR reporting programs in their countries. [14][15][16] In addition to awareness among community pharmacists, the role of regulatory authorities is also questionable due to the lack of implementation of regulations in community pharmacy practice. 10 The survey included community pharmacist's from one city in Saudi Arabia which limits its generalization.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that lethargy, lack of interest 35 , differences in the pattern of drug use, attitudes and knowledge of pharmacovigilance and different points of view among HCPs might be the contributing factors 38 , 40 . Studies conducted in Denmark and UAE reported the reasons for under-reporting to be contributed by; the complexity of the reporting process and lack of reporting skills 41 , lack of time, other priorities, uncertainty concerning the drug causing the ADE, difficulty in accessing reporting forms, lack of awareness of the requirements for reporting and lack of understanding of the purpose of spontaneous reporting 24 . Likewise, other factors include unknown reporting procedures, unavailability of reporting forms, and lack of time as also reported in a study conducted in Vietnam 42 , lack of time to complete a report, lack of confidence to discuss ADRs, reporting generate extra work, concern report may be wrong and single ADR report may not affect the database as it was reported in a study conducted in South Africa 30 .…”
Section: Discussionmentioning
confidence: 99%